2020
DOI: 10.1002/nme.6436
|View full text |Cite
|
Sign up to set email alerts
|

Development of computationally efficient augmented Lagrangian SPH for incompressible flows and its quantitative comparison with WCSPH simulating flow past a circular cylinder

Abstract: SummaryIn Lagrangian particle‐based methods such as smoothed particle hydrodynamics (SPH), computing totally divergence‐free velocity field in a flow domain with the smallest error possible is the most critical issue, which might be achieved through solving pressure Poisson equation implicitly with higher particle resolutions. However, implicit solutions are computationally expensive and may be particularly challenging in the solution of multiphase flows with highly nonlinear deformations as well as fluid‐stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Moreover, in order to reduce the computational costs, explicit incompressible SPH formulations are also present in the literature [22][23][24], which introduce simplifying assumptions for solving the pressure Poisson equation in an explicit fashion. Augmented Lagrangian SPH (ALSPH) is the most recent and novel explicit incompressible SPH method that has been recently introduced and further improved by the authors [25,26].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, in order to reduce the computational costs, explicit incompressible SPH formulations are also present in the literature [22][23][24], which introduce simplifying assumptions for solving the pressure Poisson equation in an explicit fashion. Augmented Lagrangian SPH (ALSPH) is the most recent and novel explicit incompressible SPH method that has been recently introduced and further improved by the authors [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Fatehi et al [25] performed simulations with the ALSPH method on 2D flow over the backward facing step and 2D pressure jump problems, when comparing the results with the weakly compressible SPH (WCSPH) method. In our recent study [26], along with algorithm enhancements and a simple adaptive scheme for the penalty term estimation, we have further investigated the performance of the ALSPH method through solving a challenging incompressible flow problem, namely, 2D flow past a circular cylinder under low to moderate Reynolds numbers. The authors [25,26] demonstrated the advantage of ALSPH over WCSPH in terms of rendering smoother pressure fields and smaller velocity divergences at the expense of a larger computational cost.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations